Da Roma a Gades gestione, smaltimento e riuso dei rifiuti artigianali e commerciali in ambiti portuali marittimi e fluviali : atti del workshop internazionale (Roma, 19-20 settembre 2019) : in omaggio a Simon Keay = la gestión, eliminación y reutilización de residuos artesanales y comerciales en ámbitos portuarios marítimos y fluviales : en homenaje a Simon Keay - Bernal Casasola, Darío 1971-; Contino, Alessia 1976-; Sebastiani, Renato (Archaeopress Publishing Ltd, 2022)
Da Roma a Gades/De Roma a Gades is dedicated to the illustrious and beloved archaeologist Simon Keay. It collects the scientific results of the International Workshop held in Rome in September 2019, which discussed the management, elimination and reuse of artisanal and commercial waste in maritime and river ports. Two relevant archaeological finds in recent years (the "Nuovo Mercato Testaccio" in Rome, focused on the recycling of rudera; and the "Halieutic Testaccio" in Gades, dedicated to waste from the fish processing industry), both currently being opened as museums, have constituted the spur to revive the discussion on the fundamental importance of ?dumps? for historical reconstruction in Antiquity. A dozen contributions from Italian, Spanish and French colleagues analyze the role of urban waste in the city from multiple perspectives, although most prominently from an archaeological point of view. From the few public examples still known in the Roman world (Monte Testaccio and the new find in Cádiz, possibly managed by that municipium in Baetica) to the problem of selected and unselected waste. Through paradigmatic examples from the Western Mediterranean (from the Palatine or Trastevere in Rome to the unique cases of Augusta Emerita or Arles) the contributors reflect on the "typology" of dumps and their importance for understanding the ways of life of past societies.
This volume, dedicated to the illustrious archaeologist Simon Keay, collects the scientific results of an international workshop held in Rome (2019), which discussed the management, elimination and reuse of artisanal and commercial waste in maritime and river ports, focussing on the Roman cities of Rome and Gades (modern day Cádiz)
Keywords: Hafen; Römerzeit; Abfall; Cádiz; Rom; Atti di congressi; Konferenzschrift -- 2019 -- Rom; Festschrift